EFFECTIVENESS OF ISLAMIC SPIRITUAL COUNSELING ON EMOTIONAL RESILIENCE OF BROKEN HOME STUDENTS - Darul Ihsan; Khamam Khosiin; Benny Prasetya (Research Psychologie, Orientation et Conseil, 2026)
This study examines the effectiveness of Islamic spiritual counseling in strengthening emotional resilience among students from broken home backgrounds in an Islamic secondary school. Using a qualitative descriptive design, data were collected through semi-structured interviews, observations, and document analysis involving students, counselors, and Islamic education teachers, and analyzed using thematic analysis. The findings indicate that Islamic spiritual counseling improves emotional regulation, adaptive coping, interpersonal adjustment, and psychological stability through spiritual reflection, value-based guidance, and empathetic counseling. Students showed increased self-awareness, better emotional control, stronger meaning-making, and higher social engagement, reflecting sustained resilience development. This study offers novelty by extending resilience theory into culturally grounded Islamic counseling practices in formal school settings and positioning spirituality as an internal regulatory and developmental resource. The results also demonstrate that institutional integration of spiritual counseling supports continuous emotional growth and positive behavioral change among adolescents experiencing family disruption. Practically, the findings provide evidence-based guidance for schools and counselors to implement holistic and culturally responsive counseling models that align psychological support with students’ spiritual identities to enhance effectiveness and sustainability.